Kejawen Spiritualism: The Actualization of Moral Values at Paguyuban Suci Hati Kasampurnan in Cilacap - Mustolehudin, Mustolehudin; Muawanah, Siti (UIN Maulana Malik Ibrahim Malang, 2017)
In Java, the existence of penghayat—believing in the One Almighty God—has grown significantly during the early reign of President Joko Widodo. This is supported by the Regulation of Ministry of Education and Culture Number 27 in 2016 about education services related to the belief in the One Almighty God at schools. Paguyupan Hati Suci Kasampurnan is one of penghayat groups in Cilacap which implements the teaching of budi pekerti (good behaviors) towards its adherents. This is a qualitative research examining the hidden meaning contained in the guidance book of Paguyupan Hati Suci Kasampurnan through semiotic analysis. This study results in two findings. First, the main source used at this paguyuban is Kitab Adam Makna. Second, the main teaching of this paguyuban is the teaching of good behaviors towards the adherents in order to reach the level of perfect life which is known as manunggaling kawula gusti. Di Jawa, keberadaan penghayat terhadap Tuhan Yang Maha Esa mengalami perkembangan yang cukup signifikan pada awal pemerintahan Presiden Joko Widodo. Hal ini dikuatkan dengan terbitnya regulasi Menteri Pendidikan dan Kebudayaan Republik Indonesia Nomor 27 Tahun 2016 tentang layanan pendidikan kepercayaan terhadap Tuhan Yang Maha Esa pada satuan pendidikan. Paguyuban Suci Hati Kasampurnan merupakan salah satu kelompok penghayat di Cilacap yang ikut berperan aktif dalam mengimplementasikan ajaran budi pekerti kepada pemeluknya. Melalui pendekatan kualitatif, penelitian ini berupaya mengkaji makna yang tersirat dalam kitab ajaran Paguyupan Hati Suci Kasampurnan melalui analisis semiotika. Hasil penelitian berupa dua temuan. Pertama, sumber ajaran Paguyuban SHK adalah Kitab Adam Makna (berupa simbol-simbol yang terdapat di jagat raya). Kedua, bahwa intisari dari ajaran paguyuban ini adalah mengajarkan budi pekerti luhur sebagai dasar untuk memperoleh kesempurnaan dengan Tuhan (manunggaling kawula gusti).